Gender, assets, and agricultural development: Lessons from eight projects - Johnson, Nancy L.; Kovarik, Chiara; Meinzen-Dick, Ruth S.; Njuki, Jemimah; Quisumbing, Agnes R. (International Food Policy Research Institute, 2015)
Ownership of assets is important for poverty alleviation, and women’s control of assets is associated with positive development outcomes at the household and individual levels. This research was undertaken to provide guidance for agricultural development programs on how to incorporate gender and assets in the design, implementation, and evaluation of interventions. This paper synthesizes the findings of eight mixed-method evaluations of the impacts of agricultural development projects on individual and household assets in seven countries in Africa and South Asia. The results show that assets both affect and are affected by projects, indicating that it is both feasible and important to consider assets in the design, implementation, and evaluation of agricultural development projects. All projects were associated with increases in asset levels and other benefits at the household level; however, only four projects documented significant, positive impacts in women’s ownership or control of assets relative to a control group, and of those only one project provided evidence of a reduction in the gender asset gap. The quantitative and qualitative findings suggest ways that greater attention to gender and assets by researchers and development implementers could improve outcomes for women in future projects.